THE MEANING OF METAPHOR IN THE JAPANESE VERSION OF THE SONG LYRICS OF KARTONYONO MEDOT JANJI (KARTONYONO DE YAKUSOKU O YABUTTA) IN CRITICAL DISCOURSE ANALYSIS - Teguh Santoso; Hendrike Priventa; Ricky Darmawan (Universitas Negeri Jakarta, 2024)
Abstract: This research is entitled 'The Meaning of Metaphor in the Japanese Version of the Song Lyrics of Kartonyono Medhot Janji (Kartonyono de Yakusoku o Yabutta) in Critical Discourse Analysis'. This research uses a qualitative descriptive method. The descriptive method refers to existing facts or phenomena that are still empirically used by the speaker, so that they can be explained as they are. This research aims to find out the meaning of the metaphor in the Japanese version of the song entitled Kartonyono de Yakusoku o Yabutta by Ryuu Hikaru. In this research, Nourman Fairclough's model of critical discourse analysis is used. In this case, the author analyzes song lyrics in the form of three text dimensions, namely: text analysis, text practice and sociocultural practice. In text analysis, this research focuses on discussing representation, relationships, identity, text practices (production and consumption) and sociocultural practices (situational, institutional and social).